Rumewok Tou: Kajian Teologis Terhadap Praktek Hidup Solidaritas di Kelurahan Woloan - Kapoh, Cindy Steva; Mawuntu , Marhaeni Luciana (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article discusses one of the ancestral cultures in Minahasa, namely Rewokan. Rewokan is a hereditary culture that has existed since ancient times, and must be maintained, maintained, preserved, and maintained. Rewokan is a positive thing, because it really helps families who are experiencing grief. By using qualitative research, it was found that Rewokan can be one of the means of comfort for families, with what families receive through existing assistance. Rewokan is not a burden or trouble for families, but it is a very helpful thing for families who are experiencing grief. In Woloan, there are two types of rewokan, namely the union (social community) and the famili-famili (family).